A Study on the Quality of Mashhur Ghairu Istilahi Hadith: Reconsidering the Stereotype of Misogynistic Hadiths - Mubarok, Frenky; Suci Muzfirah; Muidatul Faziyah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
Hadith serves as the second authoritative source of Islamic teachings after the Qur’an, functioning either to elucidate the Qur’an or to supplement aspects not explicitly addressed within it, thereby guiding the religious practices of Muslims. The Mashhur Hadith is classified as a hadith transmitted by three or more narrators in each level of its chain but does not reach the level of Mutawatir. Despite not achieving the status of Mutawatir, Mashhur Hadiths are considered valid for legal determinations. In contemporary discourse, the term “Mashhur Hadith” extends beyond its technical classification by Hadith scholars to include hadiths that have gained popularity among the general populace (‘inda lisān al-nās), referred to as Mashhur Ghairu Istilahi. This article aims to examine hadiths that are prevalent among feminists, particularly those perceived as misogynistic. Muslim feminists, in their scholarly pursuits, often utilize hadiths as foundational texts. They compile hadiths they believe contradict the principles of gender equality—labeling them as misogynistic—and conduct takhrij studies to critically analyze these hadiths, seeking arguments to support the notion of feminism within Islam.